P53 codon 72 polymorphism and its association with cervical cancer - Priyanka, A.Pavani; latha, A.Asha; Jayasri mukhi, Y.; lakshmi, J.vijaya (International Journal of Scientific Research and Management (IJSRM), 2017)
Cervical cancer frequently associated with multiple HPV types. Recent report suggests that a polymorphism of thep53 tumor suppressor gene that results in the substitution of a proline residue with an arginine at position 72 protein,it act as a risk factor in HPV associated malignancies. The present study, we examined the genotypic frequency ofthis polymorphisms in 24 patients with cervical cancer using allele-specific polymerase chain reaction to detectedP53 polymorphism at 72 codon. The frequency distribution of genotypes in cervical cancer patients as 29%(7tumors) for the arginine/arginine allele, 63% (15 tumors) for the heterozygous arginine/proline status, and 8% (2tumors) for the proline/proline allele respectively. Allele frequencies of proline and arginine at 72 codon of P53gene in proline (0.400) and arginine (0.600) in cervcal cancer patients. Statistically significant difference wasobserved between the Proline/proline, arginine/arginine and proline/arginine genotypes in cervical cancer tumors(x2=16.125; p=0.003). In our result p53 codon72 Arg homozygosites has been associated with increased riskdeveloping cervical cancer. The present study reports P53 codon 72 arginine homozygosity constitutes a risk factorfor the development of invasive cervical carcinoma.In conclusion, the P53 arginine represents a potential risk for cervical cancer development.Key words: cervical cancer , p53,codon 72 polymorphism, HPV